Genetic Passport System for Captive Falcons – Saker, Gyrfalcon and Peregrine Falcon Conservation Prospects in Russia. - Ludmila S. Zinevich; Darya N. Rozhkova; Mikhail I. Iljin; Alexander G. Sorokin (Пернатые хищники и их охрана)
DNA analysis is a “gold standard” for individual identification and parentage studies as for humans, so for animals (Saks et al., 1991). First forensic testing of the rare animal species DNA occurred in 1991 in Great Britain, when the case of illegal capture of the Peregrine Falcon (Falco peregrinus) chicks was proved by parentage testing using DNA fingerprints of birds in question and other peregrines in captivity (Shorrock, 1998). In Russia, illegal capture for foreign sales is the main threat for Saker (Falco cherrug) and Gyrfalcon (Falco rusticolus) populations (Kovács et al., 2014, Lobkov et al., 2020).